Use of acoustic reflector to make a compact photoacoustic tomography system - Kalva, Sandeep Kumar (2017)
A typical photoacoustic tomography (PAT) system uses a Q-switched Nd:YAG laser for irradiating the sample and a single-element ultrasound transducer (UST) for acquiring the photoacoustic data. Conventionally, in PAT systems, the UST is held in a horizontal position and moved in a circular motion around the sample in full 2π2π radians. Horizontal positioning of the UST requires a large water tank to house, and load on the motor is also high. To overcome this limitation, we used the UST in the vertical plane instead of the horizontal plane. The photoacoustic (PA) waves generated from the sample are directed to the detector surface using an acoustic reflector placed at 45 deg to the transducer body. Hence, we can reduce the scanning radius, which, in turn, will reduce the size of the water tank and load on the motor, and the overall conventional PAT system size can be minimized. In this work, we demonstrate that with this system configuration, we acquire nearly similar images for phantom and in vivo data as that of the conventional PAT system using both flat and focused USTs.